The Diseases Caused by Obesity during Person's Life (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article devoted on growing prevalence of obesity in humans is becoming an epidemic. Two clinical cases of constitutional exogenous obesity in adolescence presented: in the first case a patient with progressive obesity complicated by dyslipidemia, diabetes mellitus, proteinuria, polyneuritis and arterial hypertension. This is a case of progressive obesity, complicated by types of diabetes mellitus, proteinuria, polyneuritis, arterial hypertension and fatty hepatitis. The second patient had multiple gastric ulcers and disseminated hemorrhagic gastritis.